2020
DOI: 10.3390/ijerph17020409
|View full text |Cite
|
Sign up to set email alerts
|

Heat Not Burn Tobacco Product—A New Global Trend: Impact of Heat-Not-Burn Tobacco Products on Public Health, a Systematic Review

Abstract: Introduction: The use of heat-not-burn tobacco products (HnB) is being adopted increasingly as an alternative to smoking combusted products, primarily cigarettes. Substantial controversy has accompanied their marketing and use in the public health context. In this study, we aimed to consider the probable impacts of HnB tobacco products use on public health. Methods: In May 2019, we conducted a systematic review of 15 studies concerning awareness and use of IQOS (abbrv. I Quit Ordinary Smoking) selected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 29 publications
4
68
0
1
Order By: Relevance
“…Findings from selected studies suggest that HTPs may create new nicotine-addicted populations. 52) The newly planned comprehensive national health promotion plan and tobacco regulation policy should reflect the emergence of novel tobacco products. In particular, the goal of the current smoking rate should include conventional cigarettes and novel tobacco products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from selected studies suggest that HTPs may create new nicotine-addicted populations. 52) The newly planned comprehensive national health promotion plan and tobacco regulation policy should reflect the emergence of novel tobacco products. In particular, the goal of the current smoking rate should include conventional cigarettes and novel tobacco products.…”
Section: Resultsmentioning
confidence: 99%
“…The public health impact of HTPs depends not only on their harmfulness relative to traditional cigarettes but also on whether they encourage an increase or decrease in the prevalence of smoking. Findings from selected studies suggest that HTPs may create new nicotine-addicted populations [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on animals found pro-inflammatory effects and data on humans found no improvement in pulmonary function after switching from combusted to heated tobacco. Independent studies found that HNB products are likely to have the pathogenic potential for COPD development [46].…”
Section: Alternative Tobacco Productsmentioning
confidence: 99%
“…Even if the association between the use of EATCs and adverse effects for human health is still under debate, there are several recent evidences of possible negative outcomes [13][14][15]. In addition to the possible adverse effects for active smokers of EATCs (the so-called vapers), experimental evidences demonstrate that the use of these devices worsen indoor air quality determining a typical passive exposure also called Environmental Electronic Vape (EEV) exposure [16][17][18]. The results of our previous researches [2,[19][20][21] highlighted that EEV exposure to particulate matter (PM) always occurs when e-cigs are used in indoor settings.…”
Section: Introductionmentioning
confidence: 99%